Altered placental expression of PAPPA2 does not affect birth weight in mice - Christians Julian K; Wagner Pamela K (Reproductive Biology and Endocrinology, 2010)
Abstract Background Pregnancy-associated plasma protein A2 (PAPPA2) is an insulin-like growth factor binding protein (IGFBP) protease expressed in the placenta and upregulated in pregnancies complicated by pre-eclampsia. The mechanism linking PAPPA2 expression and pre-eclampsia and the consequences of altered PAPPA2 expression remain unknown. We previously identified PAPPA2 as a candidate gene for a quantitative trait locus (QTL) affecting growth in mice and in the present study examined whether this QTL affects placental PAPPA2 expression and, in turn, placental or embryonic growth. Methods Using a line of mice that are genetically homogenous apart from a 1 megabase QTL region containing the PAPPA2 gene, we bred mice homozygous for alternate QTL genotypes and collected and weighed placentae and embryos at E12.5. We used quantitative RT-PCR to measure the mRNA levels of PAPPA2, as well as mRNA levels of IGFBP-5 (PAPPA2's substrate), and PAPPA (a closely related IGFBP protease) to examine potential feedback and compensation effects. Western blotting was used to quantify PAPPA2 protein. Birth weight was measured in pregnancies allowed to proceed to parturition. Results PAPPA2 mRNA and protein expression levels in the placenta differed by a factor of 2.5 between genotypes, but we did not find a significant difference between genotypes in embryonic PAPPA2 mRNA levels. Placental IGFBP-5 and PAPPA mRNA expression levels were not altered in response to PAPPA2 levels, and we could not detect IGFBP-5 protein in the placenta by Western blotting. The observed difference in placental PAPPA2 expression had no significant effect on placental or embryonic mass at mid-gestation, birth weight or litter size. Conclusions Despite a significant difference between genotypes in placental PAPPA2 expression similar in magnitude to the difference between pre-eclamptic and normal placentae previously reported, we observed no difference in embryonic, placental or birth weight. Our results suggest that elevated PAPPA2 levels are a consequence, rather than a cause, of pregnancy complications.